2013
DOI: 10.1139/apnm-2012-0362
|View full text |Cite
|
Sign up to set email alerts
|

The effects of strength training and endurance training order on running economy and performance

Abstract: This study examined the acute effect of strength and endurance training sequence on running economy (RE) at 70% and 90% ventilatory threshold (VT) and on running time to exhaustion (TTE) at 110% VT the following day. Fourteen trained and moderately trained male runners performed strength training prior to running sessions (SR) and running prior to strength training sessions (RS) with each mode of training session separated by 6 h. RE tests were conducted at baseline (Base-RE) and the day following each sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 27 publications
2
58
0
1
Order By: Relevance
“…For the sub-maximal running performance measures, significant increases were found for the majority (except for VO 2 ) of the physiological (i.e., V E , VCO 2 , V E /VO 2 , V E /VCO 2 and HR) and perceptual (i.e., RPE) measures. These findings indicated that strength training increased the physiological cost of sub-maximal running which is similar to previous findings of elevations in cardiorespiratory parameters and RPE following lower body strength training (Doma and Deakin 2013;Burt et al 2013). Furthermore, the increase in the physiological cost of sub-maximal running with a concomitant elevation EIMD markers is in line with that of the previous studies (Chen et al 2009;Burt et al 2013;Chen et al 2007;Doma and Deakin 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For the sub-maximal running performance measures, significant increases were found for the majority (except for VO 2 ) of the physiological (i.e., V E , VCO 2 , V E /VO 2 , V E /VCO 2 and HR) and perceptual (i.e., RPE) measures. These findings indicated that strength training increased the physiological cost of sub-maximal running which is similar to previous findings of elevations in cardiorespiratory parameters and RPE following lower body strength training (Doma and Deakin 2013;Burt et al 2013). Furthermore, the increase in the physiological cost of sub-maximal running with a concomitant elevation EIMD markers is in line with that of the previous studies (Chen et al 2009;Burt et al 2013;Chen et al 2007;Doma and Deakin 2013).…”
Section: Discussionsupporting
confidence: 91%
“…These findings indicated that strength training increased the physiological cost of sub-maximal running which is similar to previous findings of elevations in cardiorespiratory parameters and RPE following lower body strength training (Doma and Deakin 2013;Burt et al 2013). Furthermore, the increase in the physiological cost of sub-maximal running with a concomitant elevation EIMD markers is in line with that of the previous studies (Chen et al 2009;Burt et al 2013;Chen et al 2007;Doma and Deakin 2013). It has been suggested that the attenuation in muscle function perturbs sub-maximal running performance as a result of EIMD (Kyrolainen et al 2000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In recent studies, these adverse effects were reflected by increased work economy when endurance loading was performed immediately after a strength loading (14) and reduced neuromuscular performance measured immediately following intensive running or cycling (27), possibly influencing physiological training adaptations. As previous studies of combined endurance and strength training have shown possible compromised adaptations in strength and power but not endurance performance (21), it is likely that the acute effects of endurance loading on strength performance are more critical for the long-term development of physical fitness than the acute effects of strength loading on work economy during endurance performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that acute strength training impaired running-time trial performance although RE was unaffected (Marcora & Bosio, 2007). A recent study examined the acute effects of the strengthand endurance-training sequence on running performance the following day (Doma & Deakin, 2013b). The results showed that RE was impaired the following day when strength training was undertaken prior to endurance training the previous day, although such results were not found with the reverse sequence.…”
mentioning
confidence: 99%